2022
DOI: 10.1097/ju.0000000000002686
|View full text |Cite
|
Sign up to set email alerts
|

Remission and Transition of Female Urinary Incontinence and Its Subtypes and the Impact of Body Mass Index on This Progression: A Nationwide Population-Based 4-Year Longitudinal Study in China

Abstract: Purpose: We estimated the remission and transition rate between urinary incontinence (UI) subtypes in women with UI and evaluated the impact of body mass index (BMI) on this process. Materials and Methods: A Chinese population-based longitudinal study was conducted. Women aged !20 years were included using a multistage, stratified, cluster sampling method. Self-reported data on demographics, medical history, and physiological and anthropometric information were collected. UI was identified using 2 questions ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Komesu et al found age between 80 and 90 and BMI over 35 to be a predictors of incident MUI, as well as lower remission rates during a 2 year follow-up [18]. In another study by Pang et al, women aged 60 or over and with BMI over 24 had a higher predicted probability of remaining with or progressing to MUI from either SUI or UUI during a 4 year follow-up [45]. Since obesity also exerts challenges to mobilizing and rehabilitating the patient after a hip fracture, and on the other hand these patients frequently suffer from malnutrition [46] and thereby might carry the risk of sarcopenic obesity [47], preventing or managing UI by weight loss presents a clinical challenge in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Komesu et al found age between 80 and 90 and BMI over 35 to be a predictors of incident MUI, as well as lower remission rates during a 2 year follow-up [18]. In another study by Pang et al, women aged 60 or over and with BMI over 24 had a higher predicted probability of remaining with or progressing to MUI from either SUI or UUI during a 4 year follow-up [45]. Since obesity also exerts challenges to mobilizing and rehabilitating the patient after a hip fracture, and on the other hand these patients frequently suffer from malnutrition [46] and thereby might carry the risk of sarcopenic obesity [47], preventing or managing UI by weight loss presents a clinical challenge in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…[41] Komesu et al found age between 80-90 and BMI over 35 to be a predictors of incident MUI, as well as lower remission rates during a 2-year follow-up [16]. In another study by Pang et al, women aged 60 or over and with BMI over 24 had a higher predicted probability of remaining with or progressing to MUI from either SUI or UUI during a 4-year follow-up [42]. The association between higher BMI and SUI did not reach statistical signi cance in our study, which might be partly explained by the sample size as well as the older age distribution of the study population compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, this study is the first to investigate the independent and combined effects of leisure-time physical activity and sedentary behavior on different subtypes of UI risk among females. UI can result in enduring physical and psychological distress for patients, with varying degrees of impact observed across different subtypes of UI [20]. In a study from China, women pointed out that the severity of mixed UI surpasses that of stress UI and urgency UI, and the overall health burden (including mental health) experienced by patients with mixed UI exceeds that of those with stress UI and urgency UI [21].…”
Section: Discussionmentioning
confidence: 99%